PELATIHAN PERAWATAN RUNNING TEXT DI DESA DUWET KECAMATAN TUMPANG - Mila Fauziyah; Ratna Ika Putri; Sidik Nurcahyo; Doddy Maulana; Indrawan Nugrahanto (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2022)
Running text has many benefits, not only can it provide beauty for a promotional media but also become a very effective promotional media and can be used for a business. In Duwet Village, there is a UMK that can produce several superior products, including corn rice (gerit), cassava crackers and bamboo crafts (besek). They need media that can be used for marketing media. With this problem, we propose running text maintenance training. Running text maintenance training for displaying information in Duwet Village is beneficial for the people there. This is due to the unavailability of running text in Duwet Village UMK. With the running text, it is expected to be able to socialize and market superior products when there are guests from outside who visit Duwet Village